2017
DOI: 10.1136/jramc-2017-000852
|View full text |Cite
|
Sign up to set email alerts
|

Retropharyngeal course of the internal carotid artery

Abstract: A 77-year-old male patient presented with dysphonia. Endoscopic examination demonstrated a distortion of the posterior pharyngeal wall, which was pulsatile. The axial CT showed left internal carotid artery in a retropharyngeal location. An anomalous course of the carotid artery in the retropharyngeal space is an unusual finding that poses a risk of vascular injury during pharyngeal surgery and intubation. Such an anomaly may be congenital (incomplete descent of the third aortic arch) and may be more pronounced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“… 5 , 6 , 8 , 18 It is the most direct route from C1, and the direction of needle entry is safe for the vertebral artery, unless there are some patients with congenital variation of blood vessels. 19 However, the needle path has a medial to lateral direction, which is often not along the long axis of the lesion. Moreover, under fluoroscopic guidance, the skull will obviously block the field of vision.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 , 8 , 18 It is the most direct route from C1, and the direction of needle entry is safe for the vertebral artery, unless there are some patients with congenital variation of blood vessels. 19 However, the needle path has a medial to lateral direction, which is often not along the long axis of the lesion. Moreover, under fluoroscopic guidance, the skull will obviously block the field of vision.…”
Section: Discussionmentioning
confidence: 99%
“…The only risk of the transoral approach regarding vascular wounds is the possibility of a retropharyngeal course of the ICA. 21 Such variation of the cervical ICA course should thus be carefully studied on the pretreatment imaging work-up. We reported in our case series only one minor complication (6.7%), which consisted in a mild retropharyngeal hematoma that spontaneously resolved without any sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…However, no direct correlation with anatomical variation and postoperative retropharyngeal hematoma have been identified. 12 - 15 The superior and inferior thyroid arteries have been identified as etiology of hemorrhage in some retrospective reviews of postoperative hematoma after ACDF, although most reported cases do not have an identifiable source of hemorrhage. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%